Pengaruh Agency Cost terhadap Kebijakan Dividen - Auditta, I Gede; Sutrisno, .; Achsin, M. (Jurnal Aplikasi Manajemen, 2014)
This study aimed to examine the effect of insider ownership, Ownership Dispersion, Free Cash Flow, Asset Collateralizable and Institutional Ownership on tigkat agency costs paid by the company, which is measured by the amount of the Dividend Payout Ratio companies listed in Indonesia Stock Exchange in the period between the years in 2008 until 2011 this type of research is to use secondary data with the model of explanation of science that aims to hypotesis testing. The data used in this study in the form of annual financial statements derived from the annual financial statements of a public company in 2008, 2009, 2010 and 2011 data collection technique used is the technique of data pooling or merging data. The results of this study indicate that the variables Insider Ownership does not have a significant effect on the Dividend Payout Ratio Asset Collateralizable while variable, instutional Ownership negative effect on Dividend Payout Ratio and Free Cash Flow positive effect on Dividend Payout Ratio.